Development of a Micro Swimming Robot Using Optimised Giant Magnetostrictive Thin Films - Y. Zhang; G. Liu; H. Li (Applied Bionics and Biomechanics)
A fish-like swimming micro robot is developed using an optimised fin actuator made of giant magnetostrictive films (GMFs). The force oscillation dynamic model of a GMF cantilever with variable cross-section area is derived, and the propulsive model of the fish robot in liquid is established. A discrete variate method for optimising caudal fin configuration is proposed to optimise its propulsive force and drive efficiency under the constraints of fixed surface area and sufficient fin end strength. Both theoretical analysis and experimental results have confirmed that the optimised caudal fin configuration can generate more powerful propulsion and improved efficiency.